Breastfeeding and infection by human immunodeficiency virus - Campos Fernandes, Regina Célia de Souza (2008)
Breastfeeding in the times of global HIV pandemia must be, over everything, a pro attitude, and responsible decision. Every effort must be towards definition of the maternal HIV infection status. In countries where there is a real possibility of guaranteeing formula feeding, health staff must indicate artificial feeding with detailed informations about its correct preparation. In cases of either suspected or confirmed maternal HIV infection, breastfeeding is contraindicated until confirmation of exclusion of HIV diagnosis. All other conducts differing from the internationally recognized recommendation outlined above ought to be repudiated.